Triple helix in the age of the fourth industrial revolution and the spatial pattern of Hungarian industry - Kiss, Eva; Varga, György; Kuttor, Dániel (ERDKUNDE, 2023)
The fourth industrial revolution is one of the most significant challenges of the past decade in Hungary as well. Its driving forces are Industry 4.0 technologies, which result in radical changes in all areas of life. This also affects the spheres of the triple helix (university-industry-government) and how they cooperate. Based on various databases and qualitative research, the main goal of the study is to explore these changes in the field of higher education in technical vocations. We will also examine how all this affects the geography of Hungarian industry. Analysing the description of the technical courses, we have identified a new course (mechatronics engineering) and a new form of training (dual training) as a response to the new technological challenges. German companies, which are at the forefront of the application of Industry 4.0 technologies, have not only encouraged the introduction of dual training, but also the cooperation between the spheres. This is evaluated from the perspective of a multi-site German company (Continental) and a university (the University of Miskolc) using the example of mechatronics engineering training to present the major characteristics of cooperation in connection with new technologies. The main result and novelty of the study is that it points out that the changes in the spheres of the triple helix and their cooperation, which were also motivated by the technological revolution, can also reshape the spatial structure of Hungarian industry.